Analisis Hukum Atas Perjanjian Kerjasama Pengelolaan Persampahan Antara Pemerintah Provinsi Sumatera Utara Dengan Pemerintah Kota Medan Berdasarkan Peraturan Daerah Nomor 6 Tahun 2015 Tentang Pengelolaan Persampahan (Studi Dinas Kebersihan Kota Medan) - Ervina Sari Sipahutar (Universitas Islam Sumatera Utara, 2021)
AbstractThe problem of waste in Indonesia is a very complex problem in a society that lacks sensitivity to the environment. Undisciplined cleanliness can create a bad atmosphere due to piles of garbage. The city development is indirectly caused by the increase in the population of the city. In this case, waste management in Medan city has a special regulation in waste management which is regulated in Regional Regulation Number 6 of 2015 concerning Solid Waste Management. It is based on Article 1 of Regional Regulation Number 6 of 2015 concerning Solid Waste Management. Therefore, Medan city government and North Sumatra provincial government made an agreement regarding the management of this waste. Regarding the form and the content of the agreement, it is submitted to the agreement of the parties conducting the agreement. Keywords : Cooperation Agreement, Waste Management, North Sumatra Provincial Government, Medan City Government